Schule entwickeln: Jahrgangsmischung in der Grundschule Eine empirische Studie zur pragmatisch bedingten Initiierung und Implementierung aus Sicht von Schulleitungen und Lehrkräften - Sonnleitner, Magdalena (Verlag Julius Klinkhardt, 2021)
"Multi-grade classes are experiencing a renaissance in the current German educational system. On the one hand, pedagogical reasons are discussed. On the other hand, the motto "short legs, short ways" as well as school organizational requirements play a decisive role. Considering the theoretical background of innovation-specific implications of multi-grade learning, the phases and conditions of school development, and the structure of professional action, the study explores how the initiation and implementation of multi-grade classes for pragmatic reasons are realized. The subquestions of the study investigate challenges of the school development process, action strategies and justifications of school administrators and teachers, their innovation-specific ideas of multi-grade learning, as well as supporting and inhibiting development conditions in the transfer of change to the individual school. For data collection eight school administrators and 16 class administrators at eight Bavarian elementary schools that had established a so-called "combi-class" 1/2 for the first time were interviewed. The transcripts were analyzed with the qualitative content analysis. In addition, an explicating document analysis was carried out. The results show that there are role-specific demands on school administrators and teachers. These are: negotiating and planning the initiation and implementation, leading and steering the development process at the individual school, and organizing and implementing the change, especially at the teaching level. The study provides an insight into individual school development processes as well as into circumstances of multi-grade learning that is ordered by school authorities due to demographic reasons or scarce personal resources. The study reveals how challenging it is for school and class administrators to broaden the age groupspecific (homogenizing) view. However, the data also show a rise in professionalization because of this school development process. Despite the top-down process of initiation, multi-grade classes can function as a motor for a changed approach to heterogeneity."